Information Seeking Problems that May Occur Against Covid-19 Vacccine When it is Ready (Medico Legal Update, 2021)
Information-seeking patterns of vaccine receivers have over time been determined their vaccine decisions.These patterns are mostly represented by their demographic representation. Therefore it is interesting toreview how these demographic representations have affected vaccine choices in the past. This paper wouldserve as a guide to health officials, human communication experts and pharmaceutical companies in thedevelopment and distribution of Coronavirus vaccines when it is ready